2018
DOI: 10.1002/cnma.201800161
|View full text |Cite
|
Sign up to set email alerts
|

Dealloyed Nanoporous Gold Catalysts: From Macroscopic Foams to Nanoparticulate Architectures

Abstract: Dealloyed nanoporous Au membranes and spongy Au nanoparticles exhibit a set of unique structural features highly desirable for heterogeneous catalysis and electrocatalysis. In this Focus Review, we present the state‐of‐the‐art understanding of the complex mechanisms dictating the nanoscale porosity evolution during percolation dealloying of alloys and the structure‐composition‐performance correlations underpinning the catalytic behaviors of dealloyed nanoporous Au. We focus on several fundamentally intriguing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 92 publications
(198 reference statements)
0
20
0
Order By: Relevance
“…The mechanisms underpinning the versatile structural transformations of AuCu 3 alloy NPs observed in polyol solvents could be interpreted in the context of the interplay among Cu–Pt galvanic exchange, oxidative etching of Cu, and seed-mediated deposition of Pt. Upon exposure to an appropriate oxidative etching environment, Au–Cu alloys with Cu atomic fraction above the parting limit (∼70 atom % of Cu) undergo percolation dealloying to evolve into bicontinuous nanoporous structures composed of nanoligaments that are compositionally Au-rich. , The structural evolution of an alloy NP during percolation dealloying can be rigorously described using Erlebacher’s surface diffusion continuum model . The percolation dealloying of an Au–Cu alloy NP is initiated upon oxidative etching of Cu atoms at the NP/electrolyte interfaces, whereas the undercoordinated Au surface atoms left behind the dealloying frontier undergo rapid surface migration to form Au-rich patchy islands that locally protect the NP surfaces from further etching.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The mechanisms underpinning the versatile structural transformations of AuCu 3 alloy NPs observed in polyol solvents could be interpreted in the context of the interplay among Cu–Pt galvanic exchange, oxidative etching of Cu, and seed-mediated deposition of Pt. Upon exposure to an appropriate oxidative etching environment, Au–Cu alloys with Cu atomic fraction above the parting limit (∼70 atom % of Cu) undergo percolation dealloying to evolve into bicontinuous nanoporous structures composed of nanoligaments that are compositionally Au-rich. , The structural evolution of an alloy NP during percolation dealloying can be rigorously described using Erlebacher’s surface diffusion continuum model . The percolation dealloying of an Au–Cu alloy NP is initiated upon oxidative etching of Cu atoms at the NP/electrolyte interfaces, whereas the undercoordinated Au surface atoms left behind the dealloying frontier undergo rapid surface migration to form Au-rich patchy islands that locally protect the NP surfaces from further etching.…”
Section: Results and Discussionmentioning
confidence: 99%
“…They range from catalysis, sensors (mechanical/chemical), materials for energy conversion to bio‐related applications. There are several review articles, book chapters, and monographs already published regarding NPG preparation, characterization, and applications [3–9] . Especially, a review article was recently published by our research group for applications to sensors and catalysis in general along with improvements of the preparation method of NPG [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoporous electrodes have also been shown to reduce the overpotential required to oxidize many kinetically slow redox molecules. As a result, they have been used in electrochemical sensing, catalysis, and biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…As a result, they have been used in electrochemical sensing, catalysis, and biomedical applications. [2][3][4][5] Recently, we and others have shown that such electrodes also exhibit a unique biosieving mechanism such that redox measurements can be made in biofouling solutions without coatings and with minimal loss of the electrochemical response. [6][7][8] This capability results from the morphology of nanoporous gold (NPG), which allows small redox molecules into the porous network to exchange electrons while restricting large proteins.…”
Section: Introductionmentioning
confidence: 99%